Developing Computer-Assisted Tutorial Instructional Program for Teaching Grammar In Higher Education - Untari, Elizabeth Bunga Dwi; *, Ngadiso; Asib, Abdul (Proceeding of International Conference on Teacher Training and Education, 2016)
The aims of this research were to: (1) gain information on the existing condition of learning media which areÂ used by lecturers to teach grammar, (2) develop the proper media which is suitable for the studentsâ need andÂ appropriate to teach grammar, and (3) find out the feasibility of the proposed media. Research andÂ Development method was used in this research. The research consisted of exploration stage and developmentÂ stage. Observation, questionnaire, and interview were used to gain the data, while Spiral Data Analysis wasÂ used to analyze the data. From the exploration stage, it was found out that the media usually used by theÂ lecturer to teach grammar were Power Point Presentation and handouts. The weaknesses of these media wereÂ lecturer dependent, bad presentation, time consuming, non-independent learning, device malfunction, and limited exercises. It was also revealed that Computer Assisted Instruction was not used to teach grammarÂ while it was needed. Moodle based English Grammar Gate was designed as an answer to the studentsâ need. ItÂ consisted of two major parts; they are: tutorial part and exercise part. Expert judgment was done to validateÂ the product. The experts suggested several improvements and revision was made regarding the evaluationÂ given. The revised product was then used in field testing to find out the feasibility of the product. Facing twoÂ field testing processes and having several revision toward the product, it was then stated feasible.